Hubungan Quality Of Work Life Dengan Kebahagiaan Di Tempat Kerja Pada Pegawai Kantor Wilayah Kementerian Agama Provinsi Sumatera Barat - Salsyabila, Nabila; Winbaktianur, Winbaktianur; Ruaidah, Ruaidah (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
Happy individuals tend to be more productive at work because they don't have feelings of worry about their work so that their attention can focus on work. Happiness at work can be achieved by having quality of work life in individuals. This study aims to look at the relationship between quality of work life and happiness at work among employees of the Regional Office of the Ministry of Religion, West Sumatra Province. This study uses a quantitative method with a correlational type. The sample in this study were 131 employees at the Regional Office of the Ministry of Religion of West Sumatra Province. The sampling technique used is non-probability with quota sampling. Data was collected using two psychological scales as measuring tools, namely the quality of work life scale and the happiness scale at work. Analysis of the research data was carried out using Pearson Product Moment correlation analysis with the Statistical Package for The Social Science (SPSS) 20.0 for windows program. The results of the study show that there is a significant relationship between quality of work life and happiness at work for employees of the Regional Office of the Ministry of Religion of West Sumatra Province. Quality of work life is in the low category and happiness at work is also in the low category.